Experimental studies on constant mass–volume depletion of gas-condensate systems - M. El Aily; M.H.M. Khalil; S.M. Desouky; M.H. Batanoni; M.R.M. Mahmoud (Egyptian Journal of Petroleum)
This paper presents a new empirical model to estimate dew point pressure Pd for gas condensate reservoirs as a function of routinely measured gas analysis and reservoir temperature. The proposed model was developed based on field and laboratory PVT analysis data of 202 gas-condensate fluid samples representing different gas reservoirs and a wide range of gas properties and reservoir temperatures. Statistical error analysis was used to determine the accuracy of the model. The evaluation shows that correlation coefficient, average relative error (ARE), and average absolute relative error (AARE) are 0.9896, −1.1% and 2.58%, respectively. In addition, results of the proposed model were compared with those published in the literature and ensured its success for capturing the physical trend of gas-condensate systems, and consequently is considered as the most reliable one for the petroleum industry. The accuracy of the model has been also compared to the Soave Redlich Kwong equation of state (SRK-EOS) and the Peng Robinson equation of state (PR-EOS). Gas condensate samples have been used to check the validity of the proposed model against EOS.